Self-Compassion: Unveiling Mental Health Through Emotion Regulation in High-school Students - Syafitri, Nellinda; Lubis, Rahmi; Indrawan, Yudistira Fauzi; Choong, Thum Chern (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2024)
This study aims to examine the effect of self-compassion on mental health, with emotion regulation as a mediator variable. Adolescents experience rapid physical, cognitive, emotional and psychological changes in themselves that have the potential to cause mental health problems. The key to success in maintaining mental health is learning to be kind and compassionate to oneself, especially in stressful and difficult situations, or self-compassion. Self-compassion plays an important role in mental health outcomes, where self-compassion will include the emotion regulation component, helping individuals to face and understand negative emotions as adaptive coping. Effective emotion regulation will shape healthy adolescents, so it is suggested that emotion regulation may mediate the influence of self-compassion on mental health. This research uses quantitative methods and was conducted on 574 high school students in Medan, aged 14-19 years. The instruments used were the Warwick Edinburg Mental Wellbeing Scale (WEMWBS), the Self-Compassion Scale, and the Emotion Regulation Scale. The results of the mediation analysis using PLS-SEM4 show that emotion regulation significantly mediates the influence between self-compassion and mental health (T-statistic = 3.694 > 1.96 and P-values = .000 < .05). The results showed that emotion regulation plays a partial role in the effect of self-compassion on mental health. Adolescents who practise self-compassion will try to develop positive thinking skills and reduce the pressure and tension resulting from negative emotions, which will ultimately improve their mental health.